Tocilizumab in the treatment of active chronic humoral rejection resistant to standard therapy - Betty Chamoun; Pablo Sánchez-Sancho; Irina B. Torres; Alejandra Gabaldon; Manel Perelló; Joana Sellarés; Francesc Moreso; Daniel Serón (Nefrología (English Edition), 2022)
Introduction: There is no consensus on the most appropriate treatment for chronic active antibody-mediated rejection (cAMR). Recent studies suggest that treatment with tocilizumab (TCZ) may stabilize graft function, decrease the intensity of donor-specific HLA antibodies (DSAs) and reduce inflammation of microcirculation. Patients and methods: Observational study with renal allograft recipients diagnosed with cAMR (n = 5) who had not submitted a response to traditional treatment based on the combination of plasma replacements, immunoglobulins, and rituximab. Patients were told to be treated with TCZ as compassionate use in six doses per month (8 mg/kg/month). Renal function, proteinuria, and the intensity of DSAs were monitored during follow-up. Results: Five patients, average age 60 ± 13 years, three male and two retrasplants (cPRA average 55%) with preformed DSAs. Treatment with TCZ was initiated within 47 ± 52 days of biopsy. In two cases treatment was discontinued after the first dose, by severe bicitopenia with cytomegalovirus viremia and by graft failure, respectively. In the three patients who completed treatment, no stability of renal function (serum creatinine from 1.73 ± 0.70 to 2.04 ± 0.52 mg/dL, e-FGR 4 6 ± 15 to 36 ± 16 mL/min), showed increased proteinuria (3.2 ± 4.0 to 6.9 ± 11.0 g/g) and the intensity of DSAs maintain stable. No changes were observed in the degree of inflammation of microcirculation (g+pt 4.2 ± 0.8 vs. 4.3 ± 1.0) or in the degree of transplant glomerulopathy (cg 1.2 ± 0.4 vs. 1.8 ± 1.0). Conclusions: TCZ therapy does not appear to be effective in modifying the natural history of chronic active antibody-mediated rejection, does not improve the degree of inflammation of microcirculation and does not reduces the intensity of DSAs. Resumen: Introducción: No existe consenso sobre el tratamiento más adecuado para el rechazo humoral crónico activo (RHCa). Estudios recientes sugieren que el tratamiento con tocilizumab (TCZ) puede estabilizar la función del injerto, disminuir la intensidad de los anticuerpos anti-HLA donante-específicos (ADEs) y reducir la inflamación de la microcirculación. Pacientes y métodos: Estudio observacional con pacientes trasplantados renales diagnosticados de RHCa (n = 5) que no habían presentado respuesta al tratamiento tradicional basado en la combinación de recambios plasmáticos, inmunoglobulinas y rituximab. A los pacientes se les indicó tratamiento con TCZ como uso compasivo en seis dosis mensuales (8 mg/kg/mes). Durante el seguimiento se monitorizó la función renal, proteinuria y la intensidad de los ADEs. Resultados: Cinco pacientes, de edad media 60 ± 13 años, tres de género masculino y dos retrasplantes (cPRA medio 55%) con ADEs preformados. El tratamiento con TCZ se inició a los 47 ± 52 días de la biopsia. En dos casos se suspendió el tratamiento tras la primera dosis, por bicitopenia severa con viremia por citomegalovirus y por fracaso del injerto, respectivamente. En los tres pacientes que completaron el tratamiento no se observó estabilidad de la función renal (creatinina sérica [Cr-s] de 1,73 ± 0,70 a 2,04 ± 0,52 mg/dL, filtrado glomerular estimado [FGRe] de 46 ± 15 a 36 ± 16 mL/min), presentaron aumento de la proteinuria (3,2 ± 4,0 a 6,9 ± 11,0 g/g) y la intensidad de los ADEs se mantuvo estable. No se observaron cambios en el grado de inflamación de la microcirculación (glomerulitis y capilaritis peritubular [g+cpt] 4,2 ± 0,8 vs. 4,3 ± 1,0), ni en el grado de glomerulopatía del trasplante (glomerulopatía crónica [cg] 1,2 ± 0,4 vs. 1,8 ± 1,0). Conclusiones: La terapia con TCZ no parece ser eficaz en modificar la historia natural del rechazo humoral crónico activo, no mejora el grado de la inflamación de la microcirculación ni reduce la intensidad de ADEs.